Bone Marrow Transplantation in Patients With Acute Leukemia In Cuba: Results From the Last 30 Years and New Opportunities Through International Collaboration - José Carnot Uria; Calixto Hernández Cruz; Jorge Muñío Perurena; Wilfredo Torres Yribar; Jesús Diego de la Campa; Concepción del Castillo Carrillo; Yusaima Rodríguez Fraga; Julio A. López Silva; Kali Cepero Llauger; Ibis K. Pardo Ramírez; Aliette García García; Karen Sweiss; et al. (Journal of Global Oncology, 2018)
Blood and marrow transplantation (BMT) has been performed in Cuba for over 30 years with limited resources and without international relationships. Researchers from University of Illinois at Chicago and Hermanos Ameijeiras Hospital (HAH) in Havana collaborated on retrospectively analyzing 101 consecutive patients with adult acute leukemia who received BMT at HAH from June 1986 to January 2016. Of these, 82 had acute myeloid leukemia (AML) and 19 had acute lymphoblastic leukemia (ALL). BMT eligibility criteria included prior morphologic complete remission, no severe comorbidities, and age between 16 and 60 years. Patients with an HLA-matched donor received an allogeneic BMT, whereas the others received an autologous BMT. All patients received fresh stem cells from marrow (80%) or mobilized peripheral blood (19%). Of 82 patients with AML, 35 received an allogeneic (AML-allo) and 47 an autologous (AML-auto) BMT. Both groups had comparable median age (37 years) and follow-up of survivors. Overall survival (OS) was 34% in AML-allo and 38% in AML-auto. The transplant-related mortality rate was 40% in AML-allo and 17% in AML-auto, whereas the relapse-related mortality rates were 25% and 40%, respectively. Of the 19 patients with ALL, six received an allogeneic transplant. Of these, transplant-related mortality occurred in one patient and three died after disease relapse (OS, 33%). Of 13 patients who received autologous transplants, transplant-related mortality occurred in three and six died after disease relapse (OS, 31%). To our knowledge, this is the first scientific report on BMT performed in patients with acute leukemia in Cuba. The collaboration between University of Illinois at Chicago and HAH will further develop capacity building in research and implementation of new diagnostic and therapeutic strategies in Cuba.